The Bible and the Qur'an - Jomier, Jacques (San Francisco : Ignatius Press, 1959)
Examines the differences between Christian scripture and the teachings of the Qur'an, and describes how the Qur'an views Jesus and the Bible, the universal mission of the Muslims, and Islamic law.
Foreward vii -- Translator's preface xiii -- What is the Qur'an 1 -- Translations of the Qur'an 5 -- Muhammad's Universal Mission according to the Qur'an 7 -- The Qur'an appeals to the Bible 17 -- The Qur'an speaks of the Bible in high terms, but Muslims do not read the Bible 19 -- Does the Qur'an teach that the books of the Bible have been tampered with? 25 -- The Qur'an proclaims, above all, the greatness of God, One, Creator, Lord of the Universe, Almighty and Good 29 -- The Apocalyptic elements: The "Day" and the Resurrection 35 -- Retribution according to works and salvation by faith 41 -- Narratives concerning some ancient saints, especially the great biblical personages 45 -- The Qur'an, a book of apologetics 53 -- Jesus in the Qur'an 65 -- Muslim law 75 -- Muslim brotherhood 79 -- The history of the primitive Muslim community 83 -- The philosophy of the religious history of the world 89 -- Conclusion 97 -- Appendix One: Vatican II, Excerpts from Nostra Aetate, Declaration on the Relation of the Church to Non-Christian Religions, October 28, 1965, 101 -- Appendix Two: Francis Cardinal Arinze, 'Dialogue with Muslims from the point of view of the Catholic Church: Bases, Aims, "Experiences" 105 -- Appendix Three: John Paul II, "Muslim and Christian Communities Should be in Respectful Dialogue" 111 -- Appendix Four: John Paul II, "Genuine Peace is a Gift from God; I Raise My Heart and Voice with Great Intensity" 117 -- Appendix Five: Fulton J. Sheen, "Mary and the Muslims" 121 -- Updated Bibliography 127.
Includes bibliographical references (pages 127-130).
Keywords: Qurʼan -- Comparative studies; Bible -- Comparative studies; Religions -- Comparative studies